2021
DOI: 10.1186/s40101-021-00252-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between air flow limitation and body composition in young adults

Abstract: Background Body composition (BC) influences respiratory system mechanics, provoking air flow limitation (AFL). The objective of this study was to determine the relationship of AFL in small- and medium-caliber airways with BC in young adults. Methods Eighty-three individuals were recruited (40 men and 43 women). To determine AFL, the following measurements were taken: forced expiratory volume in the first second (FEV1), forced expiratory flow betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Many studies have examined the association between body composition and lung function. [10][11][12][13][14][15][16][17][18][19][20][21] The findings of a study on 7,801 Taiwanese individuals showed that BF% was inversely associated with FEV1 and FVC, even among patients with normal weight determined by BMI (18.5-24.9 kg/m). 15 In a study of 1,746 Brazilian participants, FM was reportedly inversely associated with FEV1 and FVC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have examined the association between body composition and lung function. [10][11][12][13][14][15][16][17][18][19][20][21] The findings of a study on 7,801 Taiwanese individuals showed that BF% was inversely associated with FEV1 and FVC, even among patients with normal weight determined by BMI (18.5-24.9 kg/m). 15 In a study of 1,746 Brazilian participants, FM was reportedly inversely associated with FEV1 and FVC.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have examined the association between body composition and lung function and found that FM was linearly and inversely associated with lung function [10][11][12][13][14][15][16][17][18][19][20][21] whereas FFM was linearly and positively associated with lung function. [10][11][12][13]17,[19][20][21] These findings suggest that FM and FFM may be linearly associated with lung function.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these reports did not describe model-fitting criteria in detail, it can be assumed that weight was an insignificant variable in equations and was omitted to achieve a more stable model. However, several studies have shown that body weight significantly influences the physiology of the airways [ 38 41 ] and correlates with increased airway resistance [ 42 , 43 ]. The same was observed for age because this was either deleted from equations [ 17 , 24 ] or was discriminately used for resistance or reactance [ 18 , 22 ] or a selective sex [ 19 ].…”
Section: Discussionmentioning
confidence: 99%